Organizational culture and teachers’ work motivation: Examining predictive relationships - Ratna Tri Wiharti; Ifada Novikasari (Penelitian Ilmu Pengetahuan Sosial, 2026)
Background: The role of educators is crucial in determining the success of the educational process in schools. The quality of learning delivered by teachers is directly influenced by their level of work motivation. One of the important factors affecting work motivation is organizational culture. A strong and positive organizational culture is believed to create a conducive working environment, encourage collaboration, and provide teachers with a sense of security and appreciation. However, in practice, many educators still experience demotivation due to unsupportive work cultures, such as poor communication, lack of appreciation, and excessive administrative demands. This study aims to examine the influence of organizational culture on teachers' work motivation at SMP Negeri 1 Banyumas. Methods: A quantitative approach using a survey method was employed, involving a total sampling of all 30 teachers at SMP Negeri 1 Banyumas as respondents. Data were collected through closed-ended questionnaires, and data analysis was conducted using simple linear regression to examine the relationship between organizational culture and work motivation variables. Findings: The results showed that organizational culture had a significant influence on teachers' work motivation. This was indicated by a correlation coefficient (R) value of 0.900 and a coefficient of determination (R²) value of 0.810, meaning that 81% of the variation in work motivation could be explained by organizational culture. These findings support the organizational culture theory proposed by Edgar H. Schein, which states that values, norms, and habits within an organization deeply shape members' behavior and work spirit. Conclusion: This study is expected to provide valuable input for school management in formulating policies to strengthen organizational culture in order to improve motivation, performance, and the quality of learning sustainably. Novelty/Originality of this article: The novelty of this study lies in the application of the organizational culture model as a predictor of teachers' work motivation in the context of a public junior high school, which has rarely been explored in previous empirical studies.